Supply networks: evaluation of the key-members’ logistic performance in the physical distribution of finished products - Lazzarin, Vitoria (2019)
The present article analyzes the relationship between the three main actors present in the physical distribution of final products from the perspective of supply networks: logistics operators, carriers and shippers. Questionnaires were sent to these agents, information was collected on how they value the performance criteria of the services offered and contracted, such as the fulfillment of deliveries without errors, attention to urgent requests, breakdowns and loss of goods. These criteria were analyzed from the point of view of each member of the chain that hires or provides the service. It was found that the most important criteria for shippers and carriers were those related to the attention of urgent orders and fulfillment of the delivery program, while for the logistics operators the availability of vehicles and service in period of high demand represented the most important criteria.